2016
DOI: 10.3847/0004-637x/832/2/179
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Interplanetary Intermittent Turbulence: A Case Study of Rope–rope Magnetic Reconnection

Abstract: In a recent paper, the relation between current sheet, magnetic reconnection, and turbulence at the leading edge of an interplanetary coronal mass ejection was studied. We report here the observation of magnetic reconnection at the interface region of two interplanetary magnetic flux ropes. The front and rear boundary layers of three interplanetary magnetic flux ropes are identified, and the structures of magnetic flux ropes are reconstructed by the Grad–Shafranov method. A quantitative analysis of the reconne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 56 publications
3
33
0
Order By: Relevance
“…This indicates that this interval is characterized by a higher degree of non-Gaussianity. These results are in agreement with the results of Chian et al (2016), which found that the interior of IMFR-2 has lower degrees of non-Gaussianity and phase coherence, and a nearly monofractal scaling when compared with other intervals. For the interface of IMFR-2 and IMFR-3 they observed higher degrees of non-Gaussianity and phase synchronization, and a strong departure from monofractality.…”
Section: A Triple-imfr Eventsupporting
confidence: 92%
See 4 more Smart Citations
“…This indicates that this interval is characterized by a higher degree of non-Gaussianity. These results are in agreement with the results of Chian et al (2016), which found that the interior of IMFR-2 has lower degrees of non-Gaussianity and phase coherence, and a nearly monofractal scaling when compared with other intervals. For the interface of IMFR-2 and IMFR-3 they observed higher degrees of non-Gaussianity and phase synchronization, and a strong departure from monofractality.…”
Section: A Triple-imfr Eventsupporting
confidence: 92%
“…This event was recently characterized by Chian et al (2016). They demonstrated the occurrence of magnetic reconnection at the interface region of two IMFRs and that this reconnection can be the origin of interplanetary intermittent turbulence.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations